An adaptive power split strategy with a load disturbance compensator for fuel cell/supercapacitor powertrains. (1st December 2021) - Xun, Qian; Roda, Vicente; Liu, Yujing; Huang, Xiaoliang; Costa-Castelló, Ramon
Abstract: Electric vehicles powered by fuel cell and supercapacitor hybrid power sources are of great interest. However, the power allocation between each power source is challenging and the DC bus voltage fluctuation is relatively significant in cascaded PI control schemes. This paper develops a power control strategy with an adjustable cut-off frequency, using an artificial potential field, to adaptively split the load current between the fuel cell and the supercapacitor under various load conditions. The adaptive cut-off frequency is calculated by cutting the load frequency spectrum with an allocation ratio that changes with the supercapacitor state of charge. Therefore, the relatively lower frequency portion of the load current is provided by the fuel cell and the supercapacitor handles the higher frequency portion. To enhance the control performance of the DC bus voltage regulation against the load disturbance, a load disturbance compensator is introduced to suppress the DC bus voltage fluctuation when the load variation occurs, which is implemented by a feed-forward controller that can compensate the load current variation in advance. The effectiveness of the proposed strategy is validated by extensive experiments. Highlights: The cut-off frequency is adaptively adjusted with considerations of characteristics of FC and SC. A feed-forward compensator is applied with a load disturbance observer to compensate the DC voltage variation. Experimentally verifies the effectiveness of the proposed strategy.